An Emerging Family of Piezocatalysts: 2D Piezoelectric Materials - Jin, Cheng‐Chao; Liu, Dai‐Ming; Zhang, Ling‐Xia (Small (Weinheim an der Bergstrasse, Germany), 2023)
Piezocatalysis is an emerging technique that holds great promise for the conversion of ubiquitous mechanical energy into electrochemical energy through piezoelectric effect. However, mechanical energies in natural environment (such as wind energy, water flow energy, and noise) are typically tiny, scattered, and featured with low frequency and low power. Therefore, a high response to these tiny mechanical energies is critical to achieving high piezocatalytic performance. In comparison to nanoparticles or 1D piezoelectric materials, 2D piezoelectric materials possess characteristics such as high flexibility, easy deformation, large surface area, and rich active sites, showing more promise in future for practical applications. In this review, state‐of‐the‐art research progresses on 2D piezoelectric materials and their applications in piezocatalysis are provided. First, a detailed description of 2D piezoelectric materials are offered. Then a comprehensive summary of the piezocatalysis technique is presented and examines the piezocatalysis applications of 2D piezoelectric materials in various fields, including environmental remediation, small‐molecule catalysis, and biomedicine. Finally, the main challenges and prospects of 2D piezoelectric materials and their applications in piezocatalysis are discussed. It is expected that this review can fuel the practical application of 2D piezoelectric materials in piezocatalysis. 2D piezoelectric materials constitute a promising alternative for piezocatalysis due to their inherent advantages, such as high flexibility, large surface area, and abundant active sites. In this review, the state‐of‐the‐art research progresses on 2D piezoelectric materials and their applications in piezocatalysis are summarized. The overall goal is to inspire and accelerate the practical deployment of 2D piezoelectric materials for piezocatalytic applications.